2015
DOI: 10.1111/jch.12757
|View full text |Cite
|
Sign up to set email alerts
|

Galectin‐3 Predicts Left Ventricular Remodeling of Hypertension

Abstract: Previous studies have suggested that galectin-3 is an important mediator of cardiac fibrosis. The aim of this study was to investigate the utility of galectin-3 in identifying early left ventricular remodeling (LVRM) in patients with hypertension. A total of 107 patients with hypertension and 108 controls were enrolled in this study. The levels of galectin-3 were significantly greater in hypertension patients with LVRM compared with those without LVRM. Multivariate regression analysis demonstrated that body ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
19
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 41 publications
0
19
0
1
Order By: Relevance
“…Hypertensive heart disease is one of the most common complications and can lead to death in hypertensive patients. Therefore, it is an important strategy to improve ventricular remodelling and to prevent hypertensive heart disease for the reduction of the morbidity and mortality of hypertensive patients …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypertensive heart disease is one of the most common complications and can lead to death in hypertensive patients. Therefore, it is an important strategy to improve ventricular remodelling and to prevent hypertensive heart disease for the reduction of the morbidity and mortality of hypertensive patients …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is an important strategy to improve ventricular remodelling and to prevent hypertensive heart disease for the reduction of the morbidity and mortality of hypertensive patients. [19,20] In this study, we examined the function of left ventricular at the 18, 22 and 26 weeks of age in SHRs. The results showed that the LVPW became thickened with age in the SHR group, while the EF and FS decreased, indicating that SHRs exhibited ventricular remodelling and dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…The identification of new biomarkers of subclinical cardiovascular (CV) damage allowing for improvement in CV risk estimation represents a challenging task for CV medicine. In this issue of the Journal, Yao and colleagues describe the results of a study designed to assess the role of circulating galectin‐3 (Gal‐3) in predicting abnormal left ventricular (LV) geometries (ie, concentric LV hypertrophy, eccentric LV hypertrophy, and concentric LV remodeling) in a group of essential hypertensive patients.…”
mentioning
confidence: 99%
“…In the study by Yao and colleagues, a total of 107 uncomplicated essential hypertensive patients without comorbidities (mean age 58±11 years) and 108 age‐ and sex‐matched controls (58±4 years) underwent clinic BP measurement, NT‐pro‐BNP and Gal‐3 determinations, and standard echocardiography. The major findings of this report are summarized as follows: (1) a progressive increase in circulating Gal‐3 concentrations occurred across normotensive controls (5.6 ng/mL), hypertensive patients with normal LV mass/geometry (7.3 ng/mL), and hypertensive patients with LV remodeling (12.5 ng/mL); (2) in multivariate analysis, only Gal‐3 and body mass index (BMI) were independently correlated to LV remodeling; (3) NT‐pro‐BNP did not differ in hypertensive patients with (30 pg/mL) and without (30 pg/mL) LV remodeling; and (4) receiver operating characteristic curve analyses showed that Gal‐3 performed better than NT‐pro‐BNP in detecting LV remodeling as documented by a greater area under the curve (0.698 [ P <.001] vs 0.530 [ P =.347], respectively).…”
mentioning
confidence: 99%
See 1 more Smart Citation